Zinc transporter 7 deficiency affects lipid synthesis in adipocytes by inhibiting insulin‐dependent Akt activation and glucose uptake. (12th December 2015) - Tepaamorndech, Surapun; Kirschke, Catherine P.; Pedersen, Theresa L.; Keyes, William R.; Newman, John W.; Huang, Liping
Abstract : Mice deficient for zinc transporter 7 protein (ZnT7) are mildly zinc deficient with low body weight gain and body fat accumulation. To investigate the underlying mechanism of ZnT7 deficiency in body adiposity, we examined fatty acid composition and insulin sensitivity in visceral (epididymal) and subcutaneous fat pads from Znt7 knockout and control mice. We showed that ZnT7 deficiency had adverse effects on fatty acid metabolism and insulin action in subcutaneous fat but not in epididymal fat in mice, consistent with the ZnT7 protein expression pattern in adipose tissues. Importantly, we found that the expression of ZnT7 protein was induced by lipogenic differentiation and reached a peak when the adipocyte was fully differentiated in mouse 3T3‐L1 adipocytes. We demonstrated, using Znt7 knockdown ( Znt7 KD) 3T3‐L1 adipocytes, that reduction in Znt7 expression blunted activations of the signal transduction pathways that regulated both basal and insulin‐stimulated glucose uptake in adipocytes, resulting in low glucose uptake and lipid accumulation. The expression of the signaling mediators critical for the initiation of pre‐adipocyte differentiation, including Pparγ and C/Ebpα, appeared not to be affected by Znt7 KD in 3T3‐L1 adipocytes. These findings strongly suggest a role for ZnT7 in adipocyte lipogenesis. Abstract : Znt7 knockout mice are mildly zinc deficient, accompanied with low body fat depositions. ZnT7 protein expression was significantly up‐regulated by lipogenic differentiation. Znt7 knockdown 3T3‐L1 adipocytes had low activation of Akt and Erk1/2 upon lipogenic stimulation leading to low glucose uptake and lipid synthesis in adipocytes. Our findings strongly suggest a role for ZnT7 in lipogenesis in adipocytes.